Analysis of the Impact of Using AI-Based Chatbots in Guidance and Counseling Services in Schools (International Journal of Education and Literature, 2025)
The development of information technology in the era of the Industrial Revolution 5.0 has brought significant changes to the world of education, including guidance and counseling services in schools. The use of artificial intelligence (AI)-based chatbots is an innovation that can improve the effectiveness, accessibility, and interactivity of services for students. However, on the other hand, the use of this technology also raises challenges related to ethics, privacy, and the decline of humanistic values in counseling interactions. Based on this, this study aims to analyze the positive and negative impacts of chatbots on the effectiveness of guidance and counseling services in schools. This study uses library research. Data were collected from various sources, such as books and journals related to the impact and role of chatbot use in guidance and counseling services. The results of the study show that the use of chatbots has negative and positive impacts that are very helpful and beneficial in guidance and counseling services in the current digital era, but they only function as a supporting tool and cannot replace the role of human counselors.